Techniques for Management of Portal Vein Thrombosis during Liver Transplantation - Navdeep Singh; Kenneth Washburn; Sylvester Black; Austin Schenk (Case Reports in Transplantation)
Portal vein thrombosis (PVT) poses a unique challenge in liver transplant. The management of PVT differs according to the extent of thrombosis. Anastomosis of a donor portal vein to a varix is a viable option when an adequate size varix is identified on preoperative imaging or intraoperatively. Here, we describe our experience in two liver transplant cases with cavernous transformation of the portal vein where the donor portal vein was anastomosed to a varix using a donor iliac vein interposition graft.